Up-regulation of long noncoding RNA MBNL1-AS1 suppresses breast cancer progression by modulating miR-423-5p/CREBZF axis. Issue 2 (1st February 2022) - Fang, Jun; Jiang, Gaohui; Mao, Weiguo; Huang, Lili; Huang, Chen; Wang, Shanshan; Xue, Huimin; Ke, Jing; Ni, Qichao
ABSTRACT: Breast cancer is the leading cause of cancer-related death among females, which is required to be solved urgently. Recent studies have found significant changes in a large number of genes and their transcriptional levels during breast cancer development, which are often closely related to the abnormal expression of long noncoding RNAs (lncRNAs). Herein, our study found that MBNL1-AS1 was down-regulated both in breast cancer tissues and cell lines, and it functioned as a tumor suppressor to inhibit cancer cell proliferation, migration, and invasion. MiR-423-5p was found to be a target of MBNL1-AS1 with an inverse relationship: an increase in miR-423-5p could counteract the inhibitory effect induced by MBNL1-AS1 on cancer cell promotion. Further, CREBZF was negatively regulated by miR-423-5p. Accordingly, CREBZF knockdown could impair the hindrance of cancer cell growth mediated by low miR-423-5p expression. Also, MBNL1-AS1 influenced the PI3K/AKT pathway, which was associated with cell proliferation and apoptosis, by regulating CREBZF. As a result, our work illustrated the tumor suppressor role of MBNL1-AS1 in breast cancer via upregulating miR-423-5p-targeted CREBZF. Thereby, the evidence indicates the complete understanding of the role of MBNL1-AS1/miR-423-5p/CREBZF axis in the regulation of breast cancer development, which could be used as a biomarker for predicating survival among breast cancer patients.